2012
DOI: 10.1007/s12272-012-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral evaluation of 7-O-arylmethylquercetin derivatives against SARS-associated coronavirus (SCV) and hepatitis C virus (HCV)

Abstract: Aryl diketoacid (ADK) is well known for antiviral activity which can be enhanced by introduction of an aromatic arylmethyl substituent. A natural flavonoid quercetin has a 3,5-dihydroxychromone pharmacophore which is in bioisosteric relationship with the 1,3-diketoacid moiety of the ADK. Thus, it was of our interest to test the antiviral activity of the quercetin derivatives with an arylmethyl group attached. In this study, we prepared a series of the 7-O-arylmethylquercetin derivatives with various aromatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…Scale bar: 50 μm. October 2020 | Volume 11 | Article 586331 oils against HSV type 2 (Koch et al, 2008), flavonoids quercetin against Zika virus, SARS-associated coronavirus, hepatitis C virus (HCV), and influenza A virus (Park et al, 2012;Wu et al, 2015;Wong et al, 2017). In the previous study, we explored the antiviral effects of some I. verum extracts against SGIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar: 50 μm. October 2020 | Volume 11 | Article 586331 oils against HSV type 2 (Koch et al, 2008), flavonoids quercetin against Zika virus, SARS-associated coronavirus, hepatitis C virus (HCV), and influenza A virus (Park et al, 2012;Wu et al, 2015;Wong et al, 2017). In the previous study, we explored the antiviral effects of some I. verum extracts against SGIV.…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacology studies have proved that these active compounds possess diverse pharmacological actions, including antiviral, antimicrobial, insecticidal, analgesic, antioxidant, sedative, and convulsive activities ( Chaubey, 2008 ; Dzamic et al, 2009 ; Wang et al, 2011 ; Liu et al, 2020b ). Some I. verum ingredients especially have excellent antiviral effects, such as sesquiterpenes against hepatitis B virus and HIV ( Song et al, 2007 ; Liu et al, 2015 ), essential oils against HSV type 2 ( Koch et al, 2008 ), flavonoids quercetin against Zika virus, SARS-associated coronavirus, hepatitis C virus (HCV), and influenza A virus ( Park et al, 2012 ; Wu et al, 2015 ; Wong et al, 2017 ). In the previous study, we explored the antiviral effects of some I. verum extracts against SGIV.…”
Section: Discussionmentioning
confidence: 99%
“…The same group later published the synthesis of several 7- O -arylmethylquercetin derivatives. Three of them, with 3″-Cl, 3″-CN, and 4″-Cl substituent on arylmethyl group, tested in this study showed inhibitory activity against SARS-CoV NTPase/helicase ranging between 2.7 and 5.2 μM, the same order of magnitude of the parental compound [ 63 ]. The NSP13 helicase possesses a dsDNA unwinding activity as well as an ATPase activity allowing the helicase to translocate along with the nucleic acids by hydrolyzing ATP.…”
Section: Flavonoids Against Coronavirusesmentioning
confidence: 99%
“…13 C-NMR (DMSO-D6) δ: 175.9, 163.3, 160.4, 155.9, 147.9, 147.4, 147.1, 145.05, 144.05, 136.06, 128.3, 128.3, 123.7, 123.7, 123.5, 121.75, 119.98, 115.56, 115.2, 104.3, 97.97, 92.85, 68.58, 39.84, 39.63, 39.4, 39.2, and 39; IR (KBr); ν max : 3404, 2922, 1655, 1595, 1522, 1346, and 1165 cm −1 ; and ESI-MS ( m /z): 436 [M-H] − . [ 9 ]…”
Section: Methodsmentioning
confidence: 99%